Syntheses and single crystal X-ray diffraction studies of hydroxynicotinic acid based complexes involving supramolecular interactions - Singh, S.K. (Polyhedron, 2017)
Aqua-bridged coordination polymers of Cu(II) and Cd(II) and a mononuclear complex of Cu(II) were solvothermally synthesized with hydroxy-decorated ligands such as 2-hydroxynicotinic acid (2-OHNAH) and 6-hydroxynicotinic acid (6-OHNAH) in aqueous-nonaqueous mixed media. All these complexes were characterized by elemental analyses (C, H, N), FT-IR, thermogravimetric analysis (TGA), powder XRD and single crystal X-ray crystallography. They are formulated as [Cu(2-OHNA)2] 1, [Cu(6-OHNA)2(μ-H2O)2]n 2 and [Cd(6-OHNA)2(μ-H2O)2]n 3. Complex 1 is mononuclear 0D square planar complex which extends its dimensionality by weak supramolecular interactions such as π–π stacking interactions and intermolecular hydrogen bonding. Complexes 2 and 3 are polymeric aqua-bridged 1D infinite chain of Cu(II) and Cd(II), respectively. The central metal ions in these two complexes are in octahedral coordination environment. These two complexes are also assembled by π–π stacking interactions, inter- and intramolecular hydrogen bonding interactions.
Keywords: 2-Hydroxynicotinic Acid; 6-Hydroxynicotinic Acid; Coordination polymer; Polymeric Aqua-Bridged; X-ray diffraction